Sulfurization and post-selenization of oxides precursors for high quality CuIn(S, Se)2 thin films. (15th June 2016) - Wu, Miaoju; Chen, Guilin; Wu, Xiaoping; Zhao, Jifu; Lin, Limei; Liu, Jinyang; Wang, Weihuang; Lai, Fachun
Abstract: Oxide nanoparticles-based process is one of the successful approaches to prepare CuIn1−x Gax Se2 and CuInSe2, which has achieved high power conversion efficiencies. In order to transform the oxides into selenide, the oxide precursors were annealed with solid Se which was used as a source of Se vapor rather than highly toxic and explosive H2 Se and H2 gas. However, the In2 O3 phase frequently remains in the final films after selenization because of the high stability of In2 O3 and the poor activity of Se during selenization. So, in order to eliminate the impurity phase of In2 O3 and improve the morphology of the final thin films, the oxide precursors were sequentially sulfurized and selenized. The CuIn(S, Se)2 (CISSe) thin films which have pure phase, improved crystallinity, larger grain size and optimized band gap were obtained in this work. Highlights: Sulfurization and post-selenization of oxides precursors for CISSe thin films. The oxides precursors were sulfurized to eliminate the impurity phase of In2 O3 for obtaining pure CIS phases. The CISSe films with pure phase, improved crystallinity, larger grain size, and optimized band gap were obtained.